2020
DOI: 10.1111/hex.13078
|View full text |Cite
|
Sign up to set email alerts
|

No evidence synthesis about me without me: Involving young people in the conduct and dissemination of a complex evidence synthesis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(71 citation statements)
references
References 10 publications
0
71
0
Order By: Relevance
“…Alternatives include more dialogue‐based approaches 27 or participatory codesign methods 28 . Facilitated discussions with interactive activities may be particularly suitable for working with young people 29 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatives include more dialogue‐based approaches 27 or participatory codesign methods 28 . Facilitated discussions with interactive activities may be particularly suitable for working with young people 29 …”
Section: Introductionmentioning
confidence: 99%
“…28 Facilitated discussions with interactive activities may be particularly suitable for working with young people. 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies reported a formal impact assessment of youth engagement, although four studies explored the impacts and experiences of youth engagement in research. 15 , 28 , 36 , 37 Table 4 contains a list of the impacts of youth engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Walker et al [91] Excluded Involvement of young people in research. Does not discuss higher-level involvement, including co-production.…”
Section: Simmons Et Al [80] Excludedmentioning
confidence: 99%